The dresser [videorecording (DVD)] - Eyre, Richard, 1943- (Starz Media, LLC, 2016)
One fateful night in a small English regional theatre during World War II, a troupe of touring actors stage a production of Shakespeare's "King Lear." Bombs are falling, sirens are wailing, the curtain is up in an hour but the actor/manager "Sir" who is playing Lear is nowhere to be seen. His dresser "Norman" must scramble to keep the production alive but will Sir turn up in time? And if he does, will he be able to perform that night?